Minutes to die [large type] - Sleeman, Susan (Sleeman, Susan. Homeland heroes, 2021)
"It's the intel every agent fears -- terrorists have been smuggled into the country, intent on unleashing the most deadly attack since 9/11. With the threat imminent, FBI Agent Kiley Dawson and ICE Agent Evan Bowers are charged with taking down this terrorist cell. The only problem is Kiley blames Evan for the death of her former partner, and she can barely be in the same room with him. But with millions of lives on the line, she has no choice. If it wasn't for a bad call Evan made, Kiley's former partner would still be alive, and Evan has to live with that guilt for the rest of his life. When he starts falling for her, the agent's death seems an impossible obstacle. As the terrorist plot targets Kiley's family, the two are pushed to the breaking point in a race to save countless lives."--